ANALISIS ASAS VICARIOUS LIABILITY DALAM PERTANGGUNGJAWABAN PENGGANTI ATAS PERBUATAN MELAWAN HUKUM PEGAWAI BANK - Sekar Ayu Dita, (Magister Hukum Universitas Semarang, 2023)
The purpose of this study is to describe the fulfillment of the elements and legal considerations that must be made in implementing the concept of vicarious liability related to the extent to which an employer can be held liable for harmful acts committed by employees/employees. Vicarious liability is one of the concepts in civil law that regulates the liability of substitutes committed by others. The concept of vicarious liability has been regulated in Article 1367 of the Civil Code. However, this article often causes misconceptions because there are no legal rules that further regulate the concept. There is a need for research that examines more deeply the concept of vicarious liability so that in the future these misconceptions do not occur again. This research uses a normative juridical research method using two approaches, namely the statutory approach (statue approach) and the case approach (case approach). This research analyzes the criteria that must be met in the context of substitute liability, which has not been explained in previous studies. The results of this study show that the law cannot absolutely categorize all employee actions into the responsibility of an employer. To fulfill the criteria for the application of Article 1367 of the Civil Code in a case, the injured party needs to prove that all the criteria required in the article have been fully met.